Influence of various fibers on the physico-mechanical properties of a sustainable geopolymer mortar-based on metakaolin and slag - Ziada, Mahmoud; Erdem, Savas; Gonzalez-Lezcano, Roberto Alonso; Tammam, Yosra; Unkar, Irem (Elsevier - Division Reed Elsevier India Pvt Ltd, 2023)
Recently, studies on sustainability and ecology have become widespread in almost all sectors. One of the most important reasons for this spread is the rapid increase in industrialization and, thus, the increase in waste caused by industries. In this context, significant efforts are being made to evaluate some of these wastes. One of these efforts is the production of geopolymers. In this research, metakaolin and slag-based geopolymer mortar samples were manufactured, and polyvinyl Alcohol, basalt, and macro synthetic polypropylene fibers were used to enhance the physical, mechanical, and high-temperature resistance of the sample. Physical and mechanical tests of the produced samples were performed after 28 days. Then, elevated-temperature experiments were conducted to evaluate the behavior of the fibers under the influence of high temperature. Following the high-temperature test, physical, mechanical and microstructure tests of the samples were performed. As a result, basalt fiber enhanced the compressive strength of 800 degrees C-exposed samples by 7.72% compared to the fiber-free sample. Also, polyvinyl Alcohol fiber increased the energy absorption capacity of the samples by increasing Charpy impact values to 72.22% compared to fiber-free sample. Moreover, macro synthetic polypropylene fiber reduced capillary water absorption value up to 12.44% compared to fiber-free sample.
Keywords: Geopolymer; Metakaolin; Slag; Fiber; High temperature; Sustainability